Characteristic Of Catheter Double Lumen Infection In Chronic Kidney Disease Patients At Dr. Mohammad Hoesin Hospital Palembang - Kemas Muhammad Dahlan; Fahmi Jaka Yusuf; Abdur Rahman; Ivan Rayka; Wahyu Sholekhuddin (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The majority of chronic kidney failure patients (40-60%) require hemodialysis (HD) twice a week and often face problems with inadequate venous access. Hemodialysis patients with CKD often use an alternative to central venous access in the form of a well-tunneled double lumen (CDL) catheter or non-tunneled. However, the use of CDL causes many risks of infection This study aims to analyzed risk factors for CDL infection in patients with chronic kidney failure undergoing hemodialysis at dr. Mohammad Hoesin Hospital period January to December 2021.Descriptive study with retrospective study design was undertaken in the hemodialysis unit at dr. Mohammad Hoesin Hospital Palembang from January to December 2022. There were 100 samples who met the inclusion criteria. The relationship between independent and dependent variables was analyzed using the Chi Square test or Fisher's Exact. The most important risk factors were analyzed using the Logistic Regression test. All data were analyzed by SPPS version 22.0. In this study, there was no significant relationship between gender, age, ureum, creatinine, leucocyte and length of use with the incidence of CDL infection (p > 0,05), however there is a significant relationship between nutritional status with the incidence of CDL infection (OR = 31.418 (CI5% 10.028 - 98.438); p = 0.000); there was a significant relationship between catheter location with the incidence of CDL infection (p = 0.000); and there was a significant relationship between the type of catheter with the incidence of CDL infection (OR = 32.276 (CI5% 4.096 - 254.319); p = 0.000).In this study, it was found that the factors influencing CDL infection were nutritional status and type of catheter. Keyword: Catheter, CDL, Chronic Kidney Failure, Haemodialysis, Infection